Microsatellite genotyping data for the Pacific oyster Crassostrea gigas - Cornette, Florence; Lapegue, Sylvie (SEANOE, 2020)
The Pacific oyster, Crassostrea gigas, has been voluntarily introduced from Japan and British Columbia into Europe in the early 1970s, mainly to replace the Portuguese oyster in the French shellfish industry following a severe disease outbreak. The Pacific oyster is now the species on which the European shellfish farming mostly relies on but the species is also considered as being invasive, especially in Northern Europe. Its introduction and settlement in Europe could be inferred using several types of molecular markers. Microsatellite markers being very informative with up to several tens of alleles for some loci in this species, this dataset is gathering microsatellite data at several loci genotyped in thirty European cupped oyster populations from published or unpublished projects. The added value of this dataset relies on the calibration made between the several datasets on four common markers in order to get a robust database. Method used and genotypes presentation: Thirty European cupped oyster populations were sampled for a total of 1373 individual oysters and genotyped with four microsatellite markers (see Sellos et al., 2003; Taris et al. 2005; Cornette and Lapègue, 2011; Rohfritsch et al., 2013). The genotypes are given with 6 digits, three by allele, corresponding to the estimated size of each allele. Intercalibration was performed manually between datasets in order to correctly assign allele sizes especially for alleles only separated by two base pairs. Missing data are coded with 0.